The 3rd alternative : solving life's most difficult problems - Covey, Stephen R. (Free Press, 2011)
Outlines a breakthrough approach to conflict resolution and creative problem solving that draws on the techniques of thinkers from a broad range of disciplines to explain how to incorporate diverse viewpoints for win-win solutions.